Implementation of JSIT Curriculum-Based Mathematics Learning in Forming Students Character - Tika Hildani; Islamiani Safitri (Universitas Negeri Makassar, 2021)
This study aims to describe the teaching of mathematics based on the JSIT curriculum as well as to describe the character of students in its implementation. The research focus is SMP IT Arrozaq. This research uses a qualitative approach that is descriptive. research instrument is the researcher himself. While the data collection techniques used interviews, observation, and documentation. The curriculum at SMP IT Aroozaq always adapts the learning material taught with the characteristics of an integrated Islamic school, namely integrating Islamic values or science in it and is strongly guided by the Al-Qur'an. One of the goals is that students have a good personality and character, and have clean faiths. The character values implemented at SMPIT Arrozaq can be seen from the activities that students do daily such as carrying out congregational prayers, recitations, and dhikr together, so basically all the applications that students do and carry out can be embraced to get something good